2023
DOI: 10.3389/fmicb.2023.1145673
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate-associated transcriptome reorganization in response to genomic, environmental, and evolutionary interruptions

Abstract: The genomic, environmental, and evolutionary interruptions caused the changes in bacterial growth, which were stringently associated with changes in gene expression. The growth and gene expression changes remained unclear in response to these interruptions that occurred combinative. As a pilot study, whether and how bacterial growth was affected by the individual and dual interruptions of genome reduction, environmental stress, and adaptive evolution were investigated. Growth assay showed that the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 78 publications
2
15
0
Order By: Relevance
“…It demonstrated that the chromosomal architecture of gene expression patterns remained highly conserved, regardless of the considerably varied mutations. The homeostatic periodicity was consistent with our previous findings that the chromosomal periodicity of the transcriptome was independent of genomic or environmental variation 27,28 .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It demonstrated that the chromosomal architecture of gene expression patterns remained highly conserved, regardless of the considerably varied mutations. The homeostatic periodicity was consistent with our previous findings that the chromosomal periodicity of the transcriptome was independent of genomic or environmental variation 27,28 .…”
Section: Resultssupporting
confidence: 92%
“…Genome mutation analysis and transcriptome analysis failed to identify the common gene categories or pathways that correlated to the evolution of the reduced genome; thus, the gene modules correlated to evolution were newly evaluated. The weighted gene co-expression network analysis (WGCNA) 41 was performed toward the evolved transcriptomes as tested previously 27 . Reconstruction of the 3,290 genes in the reduced genome led to 21 gene modules, comprising 8 to 320 genes per module (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcriptome datasets were deposited in the DNA Data Bank of Japan (DDBJ) under the accession number DRA013628. The differential expressed genes (DEGs) were determined using DESeq2 package [53] , with a criterion of FDR< 0.05 [54] , where the read counts were directly used, as previously described [55] . The enrichment analysis was performed using the globally normalized datasets, as previously described [49] , [56] .…”
Section: Methodsmentioning
confidence: 99%